Uma análise semântica de 'junto' e de suas variações no português brasileiro - Araújo, Ana Carolina de Sousa (Universidade Federal de São Carlos, 2024)
In this work we will carry out a semantic analysis of the expression ‘junto’ in Brazilian Portuguese (BP), taking into account its morphological characteristics, that is, its inflection in number and gender (‘juntos’, ‘juntas’) and its use in the diminutive (‘juntinho/s/as’), the different syntactic positions that the item can occupy in a sentence and the anti-distributive/collectivizing character that seems to be related to the expression. To this end, linguistic context tests will be carried out with the item JUNTO, a metaform that we will use to represent the different forms of the term, seeking to capture the different interpretations that the expression can have in BP. Having done this, we will analyze the data based on two distinct theories that were presented as a possible description for the term together, which can be understood as a close equivalent of 'junto' in English, namely, the proposal of overlapping events presented by Lasersohn (1998), and the measurement approach defended by Moltmann (2004), with the aim of discovering whether, and how, such theories can be used to explain the semantic behavior of ‘junto’ and its variations in BP. In this way, we seek to contribute not only to the description of this expression, which has not yet been studied in Brazilian Portuguese, but also to semantic studies in general.
A semantic analysis of 'junto' and its variations in Brazilian Portuguese
Keywords: Junto; Antidistributividade; Semântica; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA